How much do atmospheric depressions and Mongolian cyclones contribute to spring dust activities in East Asia? - Mu, Feifei; Fiedler, Stephanie (npj climate and atmospheric science, 2025)
Severe East Asian dust storms occur in spring due to dust-emitting winds in the Gobi Desert associated with Mongolian cyclones. The present study performs the first quantitative assessment of the contributions of Mongolian cyclones to springtime dust activity in East Asia, based on multiple reanalyses and observational datasets for 2001-2022. Atmospheric depressions dominate dust activities in Northern China, explaining ~90-92% of the total dust emissions in the Gobi Desert and ~88-93% of the dust aerosol optical depth (τ) downwind, depending on the dataset. Mongolian cyclones, defined as long-living and mobile atmospheric depressions, explain almost half (~34-47%) of the Gobi’s total dust emissions and τ downwind, and are the primary driver of high-impact dust storms. The number of Mongolian cyclones, along with the dust activity, has decreased since 2001, with a spatial pattern of the dust emission trend that is consistent with the northward shift of cyclone tracks.